Use of a Level 3 Portable Monitor for The Diagnosis and Management of Sleep-Disordered Breathing in an Inpatient Tertiary Care Setting - Marcus Povitz; R John Kimoff (Canadian Respiratory Journal)
BACKGROUND: Sleep-disordered breathing (SDB) may impact the course of medical illness among hospitalized patients. Access to testing during hospitalization to assess this may be limited by wait times for laboratory polysomnography. Level 3 portable monitoring (PM) may provide an alternative.